Underestimated Neotropical diversity: Integrative taxonomy reveals two unrelated look-alike species in a suboscine bird ( Pachyramphus albogriseus ) - Musher, Lukas J. (2023)
We applied an integrative taxonomic framework to evaluate the systematics of the Neotropical Black-and-white Becard (Pachyramphus albogriseus Sclater 1857). Combining phylogenomic (ultraconserved elements), morphological, and vocalization data, we confirmed that this species is polyphyletic; some individuals form a clade sister to P. polychopterus and should be afforded species rank as P. salvini Richmond 1899 (Slender-billed Becard), whereas the remaining subspecies of P. albogriseus (Broad-banded Becard) are sister to P. major. We found that P. salvini differs from P. albogriseus in song, color of the lores, wing-bar width, body size, and bill width. Whereas P. albogriseus occurs in montane forest in Costa Rica and Panama (ssp. ornatus) and along the eastern slope of the Andes from northern Venezuela to southern Peru (ssp. albogriseus), P. salvini is found in the lowlands from Pacific Colombia south to northwest Peru and in the Río Marañón drainage. The latter also occurs, possibly only seasonally, along the eastern slope of the Andes, where the two species’ ranges approach closely. We treat P. a. guayaquilensis Zimmer 1936 as a junior synonym of P. salvini Richmond 1899, and P. a. coronatus Phelps and Phelps 1953 as a junior synonym of P. a. albogriseus Sclater 1857. This study provides a striking example of a major problem for comparative biology: underestimated and mischaracterized diversity. We argue that there are likely many more cases like this awaiting discovery.